Sosialisasi Pencegahan Post Partum Blues Pada Ibu Nifas - Liliek Pratiwi; Uus Husni Mahmud; Raudya Setya Wismoko Putri (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2024)
.Bobak's book review (2005) states that post partum blues is a mild affective disorder syndrome that occurs early after childbirth, with signs of sadness or dysphoria, crying, irritability, anxiety, lability of feelings, tendency to blame oneself, appetite disorders. , sleep disturbances, feelings of envy and guilt. This situation will get better and worse depending on the patient's coping mechanism. By looking at this situation, we need to look at educational factors as well as being part of the factors that encourage post partum blues. Research from Hasifah, H., Nurparisih, U. S., Maliga, I., & Lestari, A. (2024), there is a relationship between the level of maternal knowledge and the incidence of post partum blues in post partum mothers. Conclusions from other research are that age, parity, level of education, family support, sleep disorders, type of delivery, and readiness to become a mother are factors that cause postpartum blues and can be overcome by involving the husband, family and the surrounding environment through support for postpartum mothers. (Olii, N et al, 2023). The method of this community service activity is by conducting outreach to post partum mothers or postpartum mothers in the Cirebon Regency area by visiting the home once. Socialization using leaflet media, with the topic, "Socialization on the Prevention of Post Partum Blues in Postpartum Women". The target selection here is postpartum mothers who have recently given birth, around 3-5 days after giving birth, targeting postpartum mothers and their husbands. After carrying out "Socialization on the Prevention of Post Partum Blues among Postpartum Mothers" through home visits, the response from families and mothers was visible. the good one. There are also several questions such as why it is so important to support postpartum mothers, there are also those who feel that they are not aware of the importance of this support, considering that the forms of support are also complex, they also feel helped by the socialization regarding the prevention of post partum blues.